Rango de acción del colocador como indicador de rendimiento en voleibol masculino - Mercado-Palomino, E.; Millán-Sánchez, A.; Parra-Royón, M.J.; Benítez, J.M.; Ureña Espa, A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2022)
This study aimed to check if the ideal setting zone is the most frequently used, to compare this zone with the Average Position of the setter with middle blocker availability (AP) and to verify if the distance between both can be considered a performance indicator. 2291 actions of the top-12 teams in the 2010 Men`s Volleyball World Championship were analysed. The position (latitude and depth) of the setter was registered. The AP and the distance with the ideal setting zone were calculated. The reception efficacy was retrieved from the FIVB. Spearman`s Rho was obtained through a correlation. Results confirm the area of latitude 6 and depth 1 as the most successful. Nevertheless, teams are able to maintain first tempo availability despite moving the setter out of it. The distance between the AP and the ideal setting zone correlates to the final ranking more than the reception efficacy.